2017
DOI: 10.20867/tosee.04.48
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Organizational Culture on Knowledge Management in Small and Medium Enterprises

Abstract: Purpose -The purpose of this work is to examine the relationship between organizational culture and knowledge management in small and medium enterprises. Organizational culture and knowledge management in today's unstable environment are becoming a major source of competitive advantage. Knowledge is an indisputable resource that allows the development of new products, creation of new ideas and strengthening the skills of people. Due to the rapid development of technology, globalization and the availability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This contention has been resonated by Pett, et al (2012) in their research revealing that these is a clear difference on learning/knowledge related aspects between SEs and MEs. This finding has been further attested by the very recent research from Klepić, et al (2020) and Tamulevičienė and Androniceanu (2020), arguing the significant difference between SEs and is a clear need to study the particularities of the relevant issues in SEs and MEs through separated research focusing on them respectively. For a manageable scale, the empirical investigation of the research reported by this paper focuses on MEs.…”
mentioning
confidence: 84%
“…This contention has been resonated by Pett, et al (2012) in their research revealing that these is a clear difference on learning/knowledge related aspects between SEs and MEs. This finding has been further attested by the very recent research from Klepić, et al (2020) and Tamulevičienė and Androniceanu (2020), arguing the significant difference between SEs and is a clear need to study the particularities of the relevant issues in SEs and MEs through separated research focusing on them respectively. For a manageable scale, the empirical investigation of the research reported by this paper focuses on MEs.…”
mentioning
confidence: 84%
“…This implies that organisational culture and structure become important considerations in KM, and HRM plays a facilitating role on these variables for effective transfer and retention of tacit knowledge in organisations. Organisational culture could positively or negatively influence and guide KM strategies and processes (Klepić & Madžar 2017). Rezaei, Jafari-Sadeghi and Bresciani (2020) asserted that the success of KM in firms often requires changes to their culture and structures.…”
Section: Literature Reviewmentioning
confidence: 99%